The Effect of Early Numerical Literacy on Early Childhood Cognitive Development - Mastikawati, Mastikawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The development of the times with increasingly advanced technology requires today’s people to be able to be literate in numeracy and master it. The low numeracy literacy activity in adults indicates a lack of stimulation given early on. This study aims to determine the effect of numeracy literacy on the cognitive development of children aged 5-6 years in Kindergartens throughout Jambi City. The subjects of this study were 31 teachers in kindergarten. Data collection techniques using a questionnaire. This research uses quantitative methods and data acquisition is analyzed using simple linear regression. Data analysis in this study used SPSS version 29. The research findings showed that there was an effect of numeracy literacy on the cognitive development of children aged 5-6 years with a calculated F value of 29.713 with a significance level of 0.